Identification of a New Candida Tropicalis Yeast Strain Possessing Antagonistic Activity Against the Spoilage Bacteria Isolated From the Fermented Vegetable Products - Mai, Nguyen Thi Thanh; Linh, Mai Thi Dam; Thu, Nguyen Phuong; Tuan, Tran Van (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: The traditional Vietnamese fermented pickles are naturally produced in presence of a microbial community including lactic acid bacteria and other microbes. Lactic acid bacteria play important roles in vegetable fermentation, whereas some yeasts have contributions to aromatic formation. However, the fermented products are sometimes spoiled by contamination of unknown bacteria during fermentation. In this study, we isolated three bacterial strains including KG 2.2, KG 2.3 and KG 2.5 in which their growth causes spoilage of the fermented pickles with formation of white biofilm layers. On basis of morphological and biochemical characteristics, these bacterial strains belong to Bacillus genus. The results from 16S rRNA gene sequencing indicated that the strains KG 2.2 and KG 2.5 are Bacillus subtilis , KG 2.3 is B. amyloliquefaciens . In addition, we isolated three antibacterial yeast strains from the high-quality fermentedvegetable samples. These yeasts are able to strongly inhibit growth of the spoilage bacteria. One of these strains with the best antagonistic activity named L36 was characterized as Candida tropicalis based on the ITS sequence of rDNA. This is the first report about Candida tropicalis having antibacterial activity against the food-spoilage bacteria. This yeast strain is a good candidate for preservation of traditional fermented vegetable products as a supplement.  Keywords: Fermented product, food-spoilage bacteria, yeast Candida tropicalis , antibacterial activity.